Realidades e perspectivas da formação contínua de professores - Maria Teresa Estrela (Universidade do Minho, 2001)
This article aims to draw up the critical balance about the present realities of the teachers in-service training in Portugal, through a succinct analysis of three levels: the reality at the level of different types of speach about in-service training; the reality at the legal level; the reality at the level of what is done. The overtaking of the detected critical points and the establishment of a necessary reinforcement of the teachers skills as curriculum designers and as aids of the pupil´s integration in the information society open some perspectives for the future.